2010
DOI: 10.1016/j.chembiol.2010.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the Ribosomal Tunnel, Nascent Chain, and Macrolides Influences Drug Inhibition

Abstract: Accumulating evidence suggests that, during translation, nascent chains can form specific interactions with ribosomal exit tunnel to regulate translation and promote initial folding events. The clinically important macrolide antibiotics bind within the exit tunnel and inhibit translation by preventing progression of the nascent chain and inducing peptidyl-tRNA drop-off. Here, we have synthesized amino acid- and peptide-containing macrolides, which are used to demonstrate that distinct amino acids and peptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 50 publications
2
70
0
7
Order By: Relevance
“…Several recent findings indicate that macrolides may inhibit translation in a polypeptide-specific manner (24,25,29,40,42). In this regard, it is noteworthy that although the affinity of CEM-101 for the ribosome in vitro is similar to that of the older macrolides, the drug has a clearly improved potency in inhibiting cell growth (26,34).…”
Section: Discussionmentioning
confidence: 98%
“…Several recent findings indicate that macrolides may inhibit translation in a polypeptide-specific manner (24,25,29,40,42). In this regard, it is noteworthy that although the affinity of CEM-101 for the ribosome in vitro is similar to that of the older macrolides, the drug has a clearly improved potency in inhibiting cell growth (26,34).…”
Section: Discussionmentioning
confidence: 98%
“…As a result, PTC inhibitors halt translation at multiple locations along the gene, whereas macrolides arrest ribosome only at a limited number of codons within the ORF, and synthesis of the proteins lacking the "problematic" sequences may not be inhibited at all (32,39). For this reason, cells treated with excess of macrolide antibiotics continue to synthesize a limited subset of polypeptides (32), whereas protein translation in cells exposed to CHL or LZD is essentially abolished (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, a growing body of evidence suggests that the synthesis of the very first 4 amino acids possesses special features. In prokaryotes, the presence of macrolides allows synthesis of at least 4 amino acids before peptidyl-tRNA release even though the macrolide binding sites is far below the PTC [26]. It has also been reported that overexpression of very short minigenes triggers ribosome drop-off.…”
Section: Discussionmentioning
confidence: 99%